R E V I E W: Genetic Diversity: Detection of Gene Variation at the DNA Level and Utilization of Gene Markers on Locating QTLs - SUTARNO SUTARNO (Society for Indonesian Biodiversity, 2003)
Advanced techniques of molecular biology have provided the opportunity to study genetic diversity within and amongbreeds at the single gene level. Many DNA markers, either of genomic DNA or cytoplasmic DNA, have been generatedrecently by utilizing molecular techniques, such as RFLP, microsatellites, PCR-RFLP, RAPD, sequencing etc. PCR-basedtechniques have recently progressed rapidly for the detection of both known- and unknown-mutation detections that may beapplied in locating gene marker for economically important traits. There are basically two different approaches of locatingquantitative trait loci (QTLs), candidate gene and random approaches. The first approach is based on prior supportingknowledge of physiological and biochemical evidence, showing that the gene is involved in the trait(s) of interest, while therandom marker approach attempts to locate gene markers by measuring genotypes at a large number of loci with unknownphenotypic effects, in the hope that the loci are linked to a QTL influencing the trait of interest.Â© 2003 Jurusan Biologi FMIPA UNS SurakartaKey words: gene variation, QTLs, gene marker.